GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PREEKLAMPSIA DI WILAYAH KERJA PUSKESMAS LEMPAKE SAMARINDA - Joanggi Wiriatarina Harianto (Universitas Muhammadiyah Kalimantan Timur, 2017)
Introduction: Preeclampsia is a desease with signs of pregnacy-induced hypertension, edema and proteinuria it becomes clear that regular and routine pregnancy care is essential in prevention of preeclampsia.Objective: this study was to determine the level of knowledge of pregnant women about preeclampsia at the Public Health Care Lempake Samarinda.Research Method: This design was use descriptive study. The population in this study was 101 pepople, and the samle was 47. Technique that was used consecutive sampling.Results: Respondents that have knowledge in a good categorie (8.5%). Respondents that have knowledge in sufficent categorie(70.2%). And respondents that have knowledge in the less categorie (21,3%) in lempake Healt center work area, based on result of research indicate that level of knowledge enough about preeclampsia.